Proteomes of the past: the pursuit of proteins in paleontology. (2nd December 2019) - Thomas, Brian; Taylor, Stephen
ABSTRACT: Introduction : Despite an extensive published literature, skepticism over the claim of original biochemicals including proteins preserved in the fossil record persists and the issue remains controversial. Workers using many different techniques including mass spectrometry, X-ray, electron microscopy and optical spectroscopic techniques, have attempted to verify proteinaceous or other biochemicals that appear endogenous to fossils found throughout the geologic column. Areas covered : This paper presents a review of the relevant literature published over the last 50 years. A comparative survey of the reported techniques used is also given. Expert opinion : Morphological and molecular investigations show that original biochemistry is geologically extensive, geographically global, and taxonomically wide-ranging. The survival of endogenous organics in fossils remains the subject of widespread and increasing research investigation.